Narcissism at the CEO–TMT Interface: Measuring Executive Narcissism and Testing Its Effects on TMT Composition - Junge, Sebastian; Graf-Vlachy, Lorenz; Hagen, Moritz; Schlichte, Franziska (Journal of Management, 2024)
Extant strategic leadership literature has established the substantial and nuanced implications of narcissism in chief executive officers (CEOs) for firm outcomes, and psychological research on narcissism in groups highlights the importance of narcissism for interpersonal dynamics. However, there is little research on strategic leaders’ narcissism and the CEO–top management team (TMT) interface, especially related to its configuration by way of TMT composition. In this article, we therefore study two issues. First, we examine how CEO narcissism directly affects two aspects of TMT composition—the narcissism of newly appointed TMT members and TMT turnover. Second, we consider the moderating effect of TMT narcissism on the relationship between CEO narcissism and TMT turnover. To be able to test our theory, we develop and extensively validate a novel measure based on LinkedIn profiles that allows us to capture the narcissism of non-CEO executives. We find substantial support for our predictions in a large sample of executives of S&P 1500 corporations across a 5-year time frame. We discuss the contributions and implications of our findings for the literatures on executive narcissism, TMT composition, and the CEO–TMT interfac
CRIS-Team Scopus Importer:2024-05-03
Keywords: narcissism; chief executive officer; top management team; CEO–TMT interface